Contribution of non-adsorbing polymers to cement dispersion. (January 2016) - Lange, A.; Plank, J.
Abstract: It has been noticed recently that at low w/c ratios (≤ 0.30), non-adsorbed polycarboxylate (PCE) polymers can contribute as well to cement dispersion. This study aimed at defining more specifically the structural requirement for such non-adsorbing polymers. For this purpose, a cement paste (w/c = 0.30) containing a conventional MPEG PCE superplasticizer was admixed with additional quantities of a polyester polymer prepared via homopolymerization of MPEG methacrylate ester macromonomer, the macromonomer used in the homopolymerization, and the polyethylene glycol contained in the macromonomer. It was found that when admixed individually, all three polymers do not adsorb on cement and cannot fluidize the paste but enhance dispersion and fluidity significantly when combined with the PCE superplasticizer. A potential explanation is that the non-adsorbing polymers act as lubricants between cement, which are particularly densely packed at low w/c ratios. The pore fluid loaded with non-adsorbed polymer exhibits superior lubrication compared to pristine cement pore solution.